Absorption spectra and band gap of thin film nanocrystalline ZnS semiconductor depos- ited at the water/toluene interface1 - Albrasi, Enteisar; Bokhamada, Hanan (Libyan Journal of Science &Technology, 2022)
This work presents a wet chemical synthesis method that uses the interface of two immiscible liquids for the formation of a thin film of nanocrystalline ZnS semiconductor at 60°C.ZnS sem- iconducting colloid nanoparticles, containing cysteine as a capping agent was deposited as a thin film at the water- toluene interface. In this method, the capped ZnS with cysteine held in contact with toluene containing octylamine. The thin film produced was characterized by UV- visible spectroscopy. The UV-Visible absorption spectra are carried out to determine the bandgap of ZnS colloid nanoparticles and a nanocrystalline thin film of ZnS. From optical ab- sorption measurements, it is clear that the direct energy gap decreases from 3.92-3.82 eV, and the size of ZnS colloid nanoparticles and nanocrystalline thin film calculated from the bandgap energy have been in the range of 3.7 - 4.2 nm.